Pengaruh Islamic Corporate Governance dan Sustainability Report sebagai Penentu Nilai Bank Umum Syariah - Arini, Arini (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to test the effects of Islamic Corporate Governance (ICG) and Sustainability Report (SR) on the value of Islamic banks. It also investigates financial performance, using Return on Assets (ROA) as a mediating variable. The research adopts a quantitative approach with a causal-explanatory design. Secondary data are employed, consisting of annual reports and sustainability reports of Islamic banks in Indonesia for the period 2021–2024, obtained from the official websites of each bank. Samples were selected using purposive sampling with the criterion that banks are publicly listed Islamic banks that consistently report both annual reports and sustainability reports during the study period. Data analysis techniques include multiple regression to test the effects of the independent variables on the dependent variable and path analysis to examine the indirect effects through the mediating variable. The results indicate that Islamic Corporate Governance (ICG) has a negative and significant effect on the value of Islamic banks, implying that higher internal governance quality is associated with a significantly lower market value in the studied sample. Conversely, Sustainability Report (SR) has a positive and significant effect on the value of Islamic banks, suggesting that a greater emphasis on structure and resource practices enhances investors’ perception of the banks’ value. The mediation analysis via path analysis reveals that financial performance, as proxied by ROA, does not mediate the effects of ICG and SR on the value of Islamic banks. These findings offer implications for the management of Islamic banks and policymakers in reviewing governance practices, sustainability reporting, and resource allocation to enhance firm value